Resíduos sólidos drenados em sub-bacia hidrográifca urbana em Santa Maria - RS - Silva, Alessandro Salles da (2010)
The inappropriate solid waste destination in urban regions create problems in streams flows such as pollution of water sources and obstruction of channels, which can cause flooding, which in addition to economic impacts, can cause severe damage to population human health . With this it is important to have tools that allow the effectiveness evaluation and the action impact in a way to generate benefits to the process of decision making by municipal managers. It is proposed in this work develop a methodology to contain the solid waste carried to Esperança s watershed, quantity and qualify these solid drainage waste SDW according to CONAMA s resolution 275 in relation to total rainfall in each event. The importance of these procedures follows the high risk of environmental damage that solid waste can cause in drainage networks. So, a sub watershed (0,57 Km2) was evaluated in the urban center of Santa Maria city, RS, using a fluviometric station with Parshall flume, where was project a structure to intercept the solid waste carried by the stream flow, it was based in collectors baskets. In accordance whith colors pattern of CONAMAS s resolution 275, it was recognized the main material in inappropriate places for people and is observed throw water resource degradation in the sub watershed. It was verify, in operational term, the efficiency of the solid waste retention strategy in isolated events, allowing people mobilization according to weather forecast. The results concerning the structure of monitoring were satisfactory, as the waste was retained in each precipitation event effectively. Monitoring of solid waste - resulted in 73% of organic matter and 27% of inorganic materials, and highlighted the significant presence of plastic was because of extensive use of this material by the population, represented 14% of the retained and the main constituents were bags groceries and bags of candy and pastries. The classification "others" was also significant, representing 6% from the total quantified and, mostly, was represented by diapers and shoes. The prediction curve of SDW is a parameter for decision to municipal managers in relation to solid waste generated within the urban basin-school, because it relates the SDW in Esperança s watershed in the stream as a function of rainfall. The total SDW loaded in one year corresponded to approximately 10.000kg with a total rainfall for the period of 1.572mm. The analysis of outcomes demonstrates a large amount of inorganic material in water quality degradation thus, questions arise about city s population environmental awareness, show up importance of environmental education actions. The identification of strong human interference reveals the environmental risks that sub watershed Esperança is submitted and results in information to support the process of municipal management of solid waste.